Réponses

2014-09-26T18:50:29+02:00
Bonsoir

A = ( 4/3 + 3/10) : (5/2 -2/5)
A = ( 40/30 + 9/30) : ( 25/10 - 4/10)
A = 49/30 : 21/10
A = 49/30 x 10/21
a = 490/630
A = 7/9

B = 5³ - (2⁴ + 7.2)²
B = 125 - ( 16 + 7.2)²
b = 125 - ( 23.2)²
B = 125 - 538.24 = - 413.24
  • Utilisateur Brainly
2014-09-26T19:26:07+02:00
A = (4/3 + 3/10) : (5/2 -2/5)
A= ((4 x 10)/(3 x 10) + (3 x 3)/(10 x 3)) : ((5 x 5)/(2 x 5) - (2 x 2)/(5 x 2))
A= (40/30 + 9/30) : (25/10 - 4/10)
A= 49/30 : 21/10
A= 49/30 x 10/21
A= 490/630
A= 49/63
A= 7/9

B = 5³ - (2⁴ + 7,2)²
B= 125 - (16 + 7,2)²
B=125 - 23,2²
B= 125 - 538,24
B= - 413,24